2007
DOI: 10.1021/ol071128p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Phosphorus Dendrimer Immobilized Azabis(oxazolines)

Abstract: Phosphorus dendrimer immobilized azabis(oxazoline) ligands can be efficiently synthesized up to the third generation with 48 ligand molecules being attached to the periphery using click chemistry. The so-assembled macromolecules were evaluated in copper(II)-catalyzed asymmetric benzoylations, showing good yields and enantioselectivities. Moreover, the copper(II)-catalysts could be readily recovered and reused in several cycles. The globular structure of the dendritic ligands seems to prevent interference of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…[7] Ligands 3 were obtained in high purity by metalation of azabis(oxazoline) 1 [8] with butyllithium and subsequent trapping with α,α'-dibromo-p-xylene, followed by recrystallization in acetone (> 80% yield).…”
Section: Design and Synthesis Of The Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] Ligands 3 were obtained in high purity by metalation of azabis(oxazoline) 1 [8] with butyllithium and subsequent trapping with α,α'-dibromo-p-xylene, followed by recrystallization in acetone (> 80% yield).…”
Section: Design and Synthesis Of The Ligandsmentioning
confidence: 99%
“…[8] The same strategy has also been described for the immobilization of other chiral ligands. [9] Copper-catalyzed [3+2]-cycloaddition [10] between 2 and two equivalents of 1,4-bis(azidomethyl)benzene were reacted to give rise to 5 in approximately 90% yield.…”
Section: Design and Synthesis Of The Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Recent studies on catalyst immobilization by us [6] and other groups [7] revealed that the copper-catalyzed azide-alkyne cycloaddition (CuAAC) is a facile method for grafting catalysts onto polymers or nanoparticles. Using an azido-functionalized support and an alkyne-substituted ligand or metal-ligand complex, high loading of the immobilized derivative close to the maximum capacity of the support can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, phosphorus dendrimer-immobilized azabis(oxazolines) form highly efficient catalysts for the asymmetric benzoylation of rac-diols with excellent recyclability. [13] In addition to the problem of leaching, the activity of an immobilized catalyst can be strongly influenced by the environment around the metal on the surface and as a result, many reactions are mass transfer limited and suffer from significant catalyst instability as well as a reduction in enantioselectivity. [14] Ionic liquids have been attracting increasing interest as a medium for catalysis as their low volatility and immiscibility with non-polar organic solvents makes them ideal candidates for catalyst immobilisa-tion and recycling.…”
Section: Introductionmentioning
confidence: 99%